An improved method for measurement of soil aggregate stability using laser granulometry applied at regional scale. (20th April 2015) - Rawlins, B. G.; Turner, G.; Wragg, J.; McLachlan, P.; Lark, R. M.
Summary Laboratory‐based aggregate stability (AS) tests should be applied to material wetted to a moisture content comparable with that of a field soil. We have improved our original laser granulometer (LG)‐based AS test published in this journal by including a pre‐wetting stage. Our method estimates disaggregation reduction (DR; µm) for a soil sample (1–2‐mm diameter aggregates). Soils with more stable aggregates have larger DR values. We apply the new technique to soils from 60 cultivated sites across eastern England, with ten samples from each of six different parent material (PM) types encompassing a wide range of soil organic carbon (SOC) concentrations (1.2–7.0%). There are large differences between the median DR values (rescaled to < 500 µm) for soils over the PM types, which when used as a predictor (in combination with SOC concentration) accounted for 53% of the variation in DR. There was no evidence for including an interaction term between PM class and SOC concentration for the prediction of DR. After applying the aggregate stability tests with the 60 regional soil samples, they were stored for 9 months and the tests were repeated, resulting in a small but statistically significant increase in DR for samples from some, but not all, PM types. We show how a palaeosol excavated from a site in southern England can be used as an aggregate reference material (RM) to monitor the reproducibility of our technique. It has been suggested that soil quality, measured by critical soil physical properties, may decline if the organic carbon concentration is less than a critical threshold. Our results show that, for aggregate stability, any such thresholds are specific to the PM.